DNA Damage and Augmented Oxidative Stress in Bone Marrow Mononuclear Cells from Angiotensin-Dependent Hypertensive Mice - Bianca P. Campagnaro; Clarissa L. Tonini; Breno V. Nogueira; Dulce E. Casarini; Elisardo C. Vasquez; Silvana S. Meyrelles (International Journal of Hypertension)
It has been proposed that the nonhemodynamic effects of angiotensin II are important for the damage observed in the two-kidney, one-clip (2K1C) renovascular hypertension model. Much evidence confirms that angiotensin II is directly involved in NAD(P)H oxidase activation and consequent superoxide anion production, which can damage DNA. The current study was performed to examine the effects of angiotensin-II-dependent hypertension in bone marrow mononuclear cells (BM-MNC); dihydroethidium staining was used to assess reactive oxygen species (ROS) production, and the comet assay was used to assess DNA fragmentation in 2K1C hypertensive mice 14 days after renal artery clipping. In this study we demonstrated that 2K1C hypertensive mice have an elevated lymphocyte count, while undifferentiated BM-MNC counts were diminished. 2K1C mice also showed an augmented ROS production and marked BM-MNC DNA fragmentation. In conclusion, endogenous renin angiotensin system activation-induced arterial hypertension is characterized by excessive ROS production in BM-MNC, which might cause marked DNA damage.